Innovative federal reserve policies during the great financial crisis - Evanoff, Douglas D; Kaufman, George G.; Malliaris, A. G. (World scientific-now publishers series in business, 2019)
This book contains discussions of unconventional monetary policies, policy changes to address systemic and payments systems risks, new macroprudential policies, the 'stretching' of the financial safety net, changes in the Fed's liquidity funding facility (the discount window), use of the Fed's balance sheet as a tool of monetary policy, and alternative means to deal with real-estate asset bubbles and potential financial instability.